2012
DOI: 10.1002/ajmg.a.35415
|View full text |Cite
|
Sign up to set email alerts
|

The Coffin–Siris syndrome: A proposed diagnostic approach and assessment of 15 overlapping cases

Abstract: Coffin-Siris syndrome (CSS) is a rare, clinically heterogeneous disorder often considered in the setting of cognitive/developmental delay and 5th finger/nail hypoplasia. Due to the clinical variability of facial and other features, this diagnosis is often difficult to confirm clinically and the existence of this disorder as a specific diagnosis has been at times an issue of debate. In an effort to further delineate the spectrum and key phenotypic features, we reviewed 80 previously reported cases to define fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 43 publications
1
74
2
1
Order By: Relevance
“…Although microcephaly has been reported as a feature of CSS [Schrier et al, 2012], we did not observe it in many patients in our previous study [Santen et al, 2013]. In our current series, only one out of 53 patients (2%) has an occipitofrontal circumference (OFC) below À2.5 SDS (Fig.…”
Section: Constitutional Featurescontrasting
confidence: 71%
See 2 more Smart Citations
“…Although microcephaly has been reported as a feature of CSS [Schrier et al, 2012], we did not observe it in many patients in our previous study [Santen et al, 2013]. In our current series, only one out of 53 patients (2%) has an occipitofrontal circumference (OFC) below À2.5 SDS (Fig.…”
Section: Constitutional Featurescontrasting
confidence: 71%
“…It is important to stress the variability of the phenotype to parents of ARID1B patients and to be aware that an ARID1B patient with CSS is different from a SMARCB1 CSS patient. For example, we have now shown that microcephaly is not a common feature in ARID1B patients, although it has been reported as a classical CSS feature [Schrier et al, 2012]. The ARID1B phenotype itself appears to be extremely broad, with the cases of CSS representing the tip of the iceberg.…”
Section: Article American Journal Of Medical Genetics Part C (Seminarmentioning
confidence: 94%
See 1 more Smart Citation
“…15 CdLS has been reported to have some clinical overlap with Fryns syndrome (coarse face, diaphragmatic hernia, cleft palate, distal limb hypoplasia and hypertrichosis), 22 foetal alcohol syndrome (pre-postnatal growth retardation, developmental delay, hirsutism, craniofacial anomalies and cardiac defects), 23 and Coffin-Siris Syndrome (aplasia or hypoplasia of the distal phalanx or nail of the fifth digit, distinctive facial features and moderate-to-severe developmental delay). 24,25 3.1.2 Describe the burden of alternative diagnostic methods to the patient The burden is minimal as clinical features are often sufficient to make a definitive diagnosis.…”
Section: Can a Diagnosis Be Made Other Than Through A Genetic Test?mentioning
confidence: 99%
“…1,2 Also, other ectodermal, constitutional and/or organ-related features may be present. 3 CSS is now classified as a BAF (also known as SWI/SNF) complex disorder, 4 as several syndrome-related genes that encode subunits of the BAF complex -ARID1A, ARID1B, SMARCA4, SMARCB1, SMARCA2 and SMARCE1 -have been identified. [5][6][7] The BAF complex modulates chromatin structure and has important roles in transcription, cell differentiation, DNA repair and tumor suppression as reviewed by Hargreaves and Crabtree.…”
Section: Introductionmentioning
confidence: 99%